Topsoil and subsoil C and N turnover are affected by superficial lime and gypsum application in the short-term - Barcelos, Jéssica P.Q. [UNESP]; Mariano, Eduardo [UNESP]; Jones, Davey L.; Rosolem, Ciro A. [UNESP] (Elsevier, 2021)
Alleviation of subsoil acidity with lime or gypsum increases carbon (C) accumulation in deep layers by stimulating root growth and C and nitrogen (N) inputs at depth. However, the effects of these amendments combined with N fertilization on soil CO2 emissions remain controversial. We evaluated the effects of superficial lime and gypsum application and N-fertilizer on C and N dynamics and microbial C use efficiency (MicCUE) in samples taken from the topsoil (0–10 cm) and subsoil (40–60 cm) of a no-till field experiment carried out in Brazil. We performed a short-term laboratory incubation with 14C-glucose and 14C-arginine to assess C and N mineralization dynamics. Liming increased topsoil pH but had no effect on subsoil acidity. A higher content of organic C, total N, and microbial biomass C and N were found in the topsoil. The addition of soil corrective (lime and gypsum) and N fertilizer had no effect on MicCUE of added 14C-glucose. However, the MicCUE of 14C-arginine was affected by the soil layer, and was higher in the subsoil. After the addition of arginine, net NH4+-N production was highest in the topsoil control, while net NO3−-N content was highest with lime + gypsum plus residual N in the same layer. We conclude that while lime and gypsum ameliorate soil acidity, they have minimal effect on C cycling through the microbial biomass, particularly in the subsoil.
Keywords: 14C-arginine; 14C-glucose; Ammonium sulphate; Carbon use efficiency; Soil acidity